Inclusion body myositis—health-related quality of life and care situation during phases of the “patience journey” in Germany: results from a qualitative study - Katja C. Senn; Simone Thiele; Laura Gumbert; Sabine Krause; Maggie C. Walter; Klaus H. Nagels (Health and Quality of Life Outcomes, 2023)
Abstract Background To understand the health-related quality of life (HRQoL) in inclusion body myositis (IBM) from a holistic perspective on the background of a complex care situation. The focus was on how the patient journey may be structured over the course of this rare disease. Methods An exploratory qualitative study was performed via in-depth semi-structured interviews. Seven patients (males n = 5) with 2011 European Neuromuscular Centre (ENMC) IBM criteria from the German IBM patient registry were interviewed for this study. The dynamic network approach of resilience and the throughput-model of health services research were used to structure the qualitative analysis. Results Our results suggest that IBM patients experience the holistic HRQoL and care situation typically in four phases: (1) uncertainty about physical vulnerability until diagnosis, (2) promising treatment approaches, (3) self-management and dyadic coping, (4) weak body, busy mind and caregiver burden. The homophonous in-vivo code “patience journey” describes the frequently reported emotional perspective of the patient journey. Although the overarching theme of perceived social support varied throughout these phases, a reliable patient-partner-dyad may lead to improved HRQoL in the long-term. Conclusions New hypotheses for future quantitative research were generated to better understand the IBM patients’ burden in the long term. The identified relevance of social support emphasizes the patients’ need to handle IBM as manageable in medical settings. During exhausting phases of IBM progression, more effective care elements for patients and their partners could disclose varying needs. Strengthening multi-professional healthcare services via individualised informational, practical, or emotional support could improve HRQoL, especially since there is no curative treatment available so far.